Anisotropic Phonon Response of Few‐Layer PdSe2 under Uniaxial Strain. (6th July 2020) - Luo, Weijun; Oyedele, Akinola D.; Gu, Yiyi; Li, Tianshu; Wang, Xingzhi; Haglund, Amanda V.; Mandrus, David; Puretzky, Alexander A.; Xiao, Kai; Liang, Liangbo; Ling, Xi
Abstract: PdSe2, an emerging 2D material with a novel anisotropic puckered pentagonal structure, has attracted growing interest due to its layer‐dependent electronic bandgap, high carrier mobility, and good air stability. Herein, a detailed Raman spectroscopic study of few‐layer PdSe2 (two to five layers) under the in‐plane uniaxial tensile strain up to 3.33% is performed. Two of the prominent PdSe2 Raman peaks are influenced differently depending on the direction of strain application. The A g 1 mode redshifts more than the A g 3 mode when the strain is applied along the a ‐axis of the crystal, while the A g 3 mode redshifts more than the A g 1 mode when the strain is applied along the b ‐axis. Such an anisotropic phonon response to strain indicates directionally dependent mechanical and thermal properties of PdSe2 and also allows the identification of the crystal axes. The results are further supported using first‐principles density‐functional theory. Interestingly, the near‐zero Poisson's ratios for few‐layer PdSe2 are found, suggesting that the uniaxial tensile strain can easily be applied to few‐layer PdSe2 without significantly altering their dimensions at the perpendicular directions, which is a major contributing factor to the observed distinct phonon behavior. The findings pave the way for further development of 2D PdSe2 ‐based flexible electronics. Abstract : The distinct anisotropic phonon response of strained few‐layer PdSe2 (two to five layers) is investigated via Raman spectroscopy. Density‐functional theory calculations reveal the near‐zero Poisson's ratios of few‐layer (one to three layers) PdSe2 . The experimental and theoretical findings are expected to facilitate further understanding of the mechanical, thermal, optical, and electronic properties of PdSe2 for future flexible electronics.